Technical Analysis and Value Investment in the Indonesia Stock Market - Maria Stevani Sianturi; Sung Suk Kim (Budapest International Research and Critics University, 2022)
This study will aim to investigate whether value investment (using buy and hold strategy by sorting portfolio based on the BM ratio) can generate excess returns in Indonesia and explore whether this value investment when combined with technical analysis (moving average indicator), can further increase the investment value in Indonesia Stock Exchange. The sample in this study includes all companies listed on the Indonesia Stock Exchange, except financial companies, for 2016 to 2021. The data obtained are analyzed using descriptive statistics, and the comparison results will see the effect of risk analyzed using regression. The analysis results show that there is no value investing effect based on the BM ratio on the Indonesian stock market. However, when the BM decile portfolio is traded with the MA (20) timing, the return of each portfolio increases compared to the trading of the BM decile strategy and shows the MA (20) strategy outperforms the buy-and-hold strategy. It was also found that this result was influenced by risk factors for each portfolio using the Fama French three-factor model.